For fun and profit: the limits and possibilities of Google-Maps-based geoweb applications. - Dalton, Craig M. (Environment & Planning A, 2015)
Software developers who create geographic web applications are a new kind of mapmaker producing new kinds of maps. They typically use private web-mapping services, such as Google Maps, without training in cartography or geographic information systems. How do software developers become mapmaking subjects producing geographic knowledges in the context of corporate mapping services? I argue that geoweb developers' subject positions and geographic knowledges are produced through the social relations of geoweb technology. Specifically, two culturally derived technical codes, playful fun and profit-seeking, are enormously influential in defining the subject positions and knowledges of geoweb applications. Utilizing both textual and in-person research, I analyze the social formation of third-party geoweb applications based on Google Maps, the social, technological limits that application developers work within, and the possibilities for developers in that context. Most developers and their knowledges stick with the technology's social codes, but a few create applications that transgress their contextual limits, opening further new possibilities for mapping, subject formation, and geographic knowledge on the web.